Researching health and internal displacement: Introduction to the special series - Jina Swartz; Bayard Roberts; David Cantor (Journal of Migration and Health)
This special series on ‘health and internal displacement’ is concerned primarily with the health needs of internally displaced persons (IDPs) in conflict contexts. Curated by editors from the recently established Health and Internal Displacement Network (HIDN), the series brings together a selection of thirteen new research articles from among many submitted in response to an open call for papers by HIDN and the Journal of Migration and Health. The aims of this series are to increase engagement with the health needs of IDPs and to support research, policy and programming in this relatively neglected area. The series focuses on IDP health but is not prescriptive in terms of health conditions, age groups, geographic region, or camp or urban setting, and reflects the diversity of IDP populations, contexts and needs.